Perancangan Sistem Pakar untuk Mendiagnosa Tingkat Stress Belajar pada Siswa SMA dengan Menggunakan Metode Forward Chaining - Amalia, Cut Rizki Putri; Mahyuddin (Design Journal, 2023)
The purpose of this research is to create an expert system using Forward Chaining to diagnose the level of learning stress in high school students using Sugeno's Fuzzy Inference System method. Data Flow Diagrams (DFD) are used to describe a data logic model or process created by the system while prototype is a development method that is used as a stage in developing applications and testing. Based on the results of research and testing of expert system design to diagnose learning stress levels in high school students using the Website-based Forward Chaining method that has been carried out by the author, several conclusions can be drawn, namely; This research succeeded in making an expert system design to diagnose the level of learning stress in high school students using the Forward Chaining method, and this study succeeded in carrying out an analysis of the results of IF THEN ELSE calculations using Forward Chaining.